Analysis of Information Technology Readiness in Furniture Business in Indonesia - Chotijah, Umi; Retrialisca, Fitri (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
Adoption of information technology (IT) can be assessed from the perspective of user readiness. This study examine the level of readiness of the Micro, Small and Medium Enterprises (MSME) furniture sector in Java in adopting IT. The design and research model was developed using the Technology Acceptance Model (TAM) and the Technology Readiness Index (TRI). Sampling uses a non-probability procedure with a purposive sampling technique. Data collection using the questionnaire survey method and analyzed using the Partial Least Square (PLS) method. In general, research findings indicate that the furniture sector SMEs in Java are prepared to adopt IT. However, research findings also indicate that the perception of discomfort and insecurity is a major issue that has the potential to hinder IT adoption by the furniture sector SMEs. Implications for stakeholders and empirical research are discussed further.